METAPHOR, PARALLELISM, AND EMOTIONAL LOAD AS STYLISTIC DEVICES IN POLITICAL DISCOURSE. - Xushvaqtova Mohira (TADQIQOTLAR, 2025)
Annotation. This article provides a comprehensive analysis of metaphor, parallelism, and emotional load as fundamental stylistic devices in political discourse. It examines the functional roles these devices play in enhancing the clarity, persuasiveness, and effective appeal of political communication. Drawing upon qualitative analysis of speeches by prominent political leaders, the study elucidates the complex interaction between linguistic form and rhetorical impact. The results contribute to a deeper understanding of how these stylistic strategies facilitate audience engagement and improve the efficacy of political messaging.